Vasutak a Dráva két partján - Majdán, János (Közép-Európai Közlemények, 2020)
The Drava River has been a border river for centuries inside the Hungarian Kingdom, but this did not prevent it from serving as a traffic corridor. In the second half of the XIXth century the new transport device, the railway was introduced to the region, though with different pace in different parts. The trains - which were relatively lesser affected by weather conditions - changed the previous traffic and transport habits and fortified new economical directions, made new settlements important. The process was sometimes characterized by accelerated expansion bringing on great transformations (til 1918), sometimes by stagnation (1920-1945) and sometimes by unpredictable decisions connected to political games (1945-1992). It is expedient to observe the railways in the valley of the Drava River because the environmental factors, that is the expansion of Croatian-Hungarian relations inside the European Union are signaling clearly that fixed track traffic can become a decisive factor - on certain lines.